2021
DOI: 10.1002/marc.202100740
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Crystalline Poly(thioether) Prepared by Visible‐Light‐Induced Organocatalyzed Thiol‐ene Polymerization in Emulsion

Abstract: A photocatalytic thiol‐ene aqueous emulsion polymerization under visible‐light is described to prepare linear semicrystalline latexes using 2,2’‐dimercaptodiethyl sulfide as dithiol and various dienes. The procedure involves low irradiance (3 mW cm−2), LED irradiation source, eosin‐Y disodium as organocatalyst, low catalyst loading (<0.05% mol), and short reaction time scales (<1 h). The resulting latexes have molecular weights of about 10 kg mol−1, average diameters of 100 nm, and a linear structure consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The melting peak was only visible in the first cycle and, therefore, the second-order transition of the glass transition temperature was more pronounced in the second heating cycle. These results indicate that the polymer contained crystalline domains during the first cycle and behaved completely as an amorphous polymer in the second heating cycle as was recently reported by Le et al [20] The crystallization kinetics were slow because of the rigidity of the polymer chains provided by the phenyl group; therefore, once the crystalline domain was molten after the first heating cycle in the DSC, the polymer did not recrystallize within the time of the cooling ramp. The same behaviour was found for all of the samples containing DATP, in which the melting peak was only visible in the first DSC cycle.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The melting peak was only visible in the first cycle and, therefore, the second-order transition of the glass transition temperature was more pronounced in the second heating cycle. These results indicate that the polymer contained crystalline domains during the first cycle and behaved completely as an amorphous polymer in the second heating cycle as was recently reported by Le et al [20] The crystallization kinetics were slow because of the rigidity of the polymer chains provided by the phenyl group; therefore, once the crystalline domain was molten after the first heating cycle in the DSC, the polymer did not recrystallize within the time of the cooling ramp. The same behaviour was found for all of the samples containing DATP, in which the melting peak was only visible in the first DSC cycle.…”
Section: Resultssupporting
confidence: 84%
“…The same authors described the photocatalytic thiol‐ene emulsion polymerization of the dithiol 2,2′‐dimercaptodiethyl sulphide with various dienes. [ 20 ] These emulsion polymerizations were carried out at a solids content of 10 wt.%. They obtained particle sizes in the range of 70–230 nm and number‐average molar masses between 7500 and 1000 g/mol.…”
Section: Introductionmentioning
confidence: 99%
“…Thiol−ene chemistry has become a versatile approach for synthesizing polythioethers. Photochemically or thermally initiated, 46,47 thiol−ene polymerizations involving bifunctional thiol and ene monomers allowed generating highly linear polymers either in solution or in dispersed systems. 46−49 It is thus an attractive approach for synthesizing a series of linear polythioethers by varying the choice of the R and R′ spacer groups in the dithiol (HS-R-SH) and the diene (H 2 C�CH-R′-CH�CH 2 ) monomers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thiol–ene chemistry has become a versatile approach for synthesizing polythioethers. Photochemically or thermally initiated, , thiol–ene polymerizations involving bifunctional thiol and ene monomers allowed generating highly linear polymers either in solution or in dispersed systems. It is thus an attractive approach for synthesizing a series of linear polythioethers by varying the choice of the R and R′ spacer groups in the dithiol (HS-R-SH) and the diene (H 2 CCH-R′-CHCH 2 ) monomers. All the resulting step polymers are made up of linear chains with the expected repeat units (−S-R-S-CH 2 -CH 2 -R′-CH 2 -CH 2 ). , In the present study, we examined the crystallization behavior of linear polythioethers which combine a variant of diethyl sulfide (dES) monomers with various monomers incorporating variants of the ethylene-oxide motif (vEO) in a precisely alternating fashion, resulting in alternating copolymers with regular molecular structures akin to poly­(ethylene oxide- alt- ethylene sulfide).…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization technologies have recently focused on thiol–ene chemistry. Historically, this polymerization approach has been used mainly in bulk or solution for applications such as coatings or surface modification. ,,, Aiming to make the process more eco-friendly, there has been a growing interest in thiol–ene polymerization in aqueous dispersed media, such as emulsion and miniemulsion. ,, Le et al reported the synthesis of polythioethers with high sulfur content. Such polymers have the ability to crystallize, yielding semicrystalline properties which are directly related to their chemical and mechanical resistance . The characterization of newly synthesized materials, mainly when specific applications are targeted such as barrier coatings or materials with high mechanical resistance, requires a comprehensive understanding of their crystallization behavior.…”
Section: Introductionmentioning
confidence: 99%